IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - M. Arif Khoiruddin; Dina Dahniary Sholekah (Nurul Jadid University, 2019)
The objective of this research is to identify the Islamic Education implementation in the field of shaping students’ religious characters applies in PGRI Vocational School of Kediri 2. The research design is descriptive qualitative and the approach applied is based on the design. The techniques of collecting data are observation, interview, and documentation. The data analysis is a qualitative descriptive analysis technique. The result of the research indicates that the religious character process is done from the start of the class to the end each day.